The effect of competition phase loads on anaerobic effort in Algerian football players - guerione, khaled (sports creativity, 2025)
The tests were conducted on a research sample of 12 players from the Ben Aknoun senior team, belonging to the National Third Division Central League, who completed a general and specific physical preparation phase over a period of two months. This phase aimed to prepare the players in terms of general and specific physical conditioning, as well as technical and tactical aspects, with 10 friendly matches played in the pre-competition phase.